2023
DOI: 10.3390/ijms241311143
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Complex Alterations in Tumors with Rhabdoid Features: Novel Therapeutic Approaches and Opportunities for Adoptive Cell Therapy

Juan José Soto-Castillo,
Lucía Llavata-Marti,
Roser Fort-Culillas
et al.

Abstract: The SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin-remodeling complex is one of the most remarkably altered epigenetic regulators in cancer. Pathogenic mutations in genes encoding SWI/SNF-related proteins have been recently described in many solid tumors, including rare and aggressive malignancies with rhabdoid features with no standard therapies in advanced or metastatic settings. In recent years, clinical trials with targeted drugs aimed at restoring its function have shown discouraging results. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…The biological mechanisms driving the antitumor activity of ICIs in SMARCA4-UT are not yet understood; abnormalities in the SWI/SNF complex correlate with enhanced interferon-gamma-induced T-cell cytotoxicity and better outcomes concerning ICIs in other malignancies [ 77 , 78 ] An enriched Th1 and cytotoxic T-cell microenvironment was recently reported in four cases of SMARCA4-deficient SCCOHT with prolonged responses to ICIs [ 77 ]. To the best of our knowledge, only one study has reported a low response rate to ICIs in SMARCA4-UT, which was associated with an absence of tumor-infiltrating lymphocytes in the TME [ 79 ] Conversely, Hozumi et al [ 80 ] showed that low SMARCA4 expression correlates with the upregulation of the T cell effector; the mature B cell marker; and central memory marker genes, such as CD8B, CD40LG, CD20, CD38, CD79, interferon Regulatory Factor 4, CD27, and -C motif chemokine receptor 7.…”
Section: Treatment: Chemotherapy Versus Immunotherapymentioning
confidence: 99%
“…The biological mechanisms driving the antitumor activity of ICIs in SMARCA4-UT are not yet understood; abnormalities in the SWI/SNF complex correlate with enhanced interferon-gamma-induced T-cell cytotoxicity and better outcomes concerning ICIs in other malignancies [ 77 , 78 ] An enriched Th1 and cytotoxic T-cell microenvironment was recently reported in four cases of SMARCA4-deficient SCCOHT with prolonged responses to ICIs [ 77 ]. To the best of our knowledge, only one study has reported a low response rate to ICIs in SMARCA4-UT, which was associated with an absence of tumor-infiltrating lymphocytes in the TME [ 79 ] Conversely, Hozumi et al [ 80 ] showed that low SMARCA4 expression correlates with the upregulation of the T cell effector; the mature B cell marker; and central memory marker genes, such as CD8B, CD40LG, CD20, CD38, CD79, interferon Regulatory Factor 4, CD27, and -C motif chemokine receptor 7.…”
Section: Treatment: Chemotherapy Versus Immunotherapymentioning
confidence: 99%